Design of Automatic Door Lock Control System Library Nurul Jadid University Based On Arduino Uno R3 and QR-Code - Moch Badrus Sholeh; Amalia Herlina; Fuad Hasan (Universitas Ahmad Dahlan, 2020)
The Nurul Jadid University Library (UNUJA) currently requires valid visitor data, because the number of visitors is an indicator of library performance in terms of disciplining staff/employees. For this reason, the UNUJA library requires an automatic library door lock control system using Arduino Uno and QR-Code. In designing tools, Arduino Uno and QR-Code are integrated with the library database application. Based on testing and analysis, it can be obtained that the success rate of testing tools in reading QR-code is 100 percent. The conclusion is that the assembly of the library door lock control system based on Arduino Uno and integrated QR-Code with the database has been able to read digital input and output.